Effects of tomato pulp addition on the extrudate quality parameters and effects of extrusion on the functional parameters of the extrudates. (7th September 2013) - Caltinoglu, Cagla; Tonyalı, Bade; Sensoy, Ilkay
Summary Effects of addition of tomato pulp on the quality parameters of the extrudates, and effects of extrusion on the functional properties of the extrudates were investigated. Bulk density, volume expansion index, longitudinal expansion index and porosity did not indicate a significant difference between the extrudates with or without tomato pulp. Sectional expansion index showed a slight increase with pulp addition. Textural analysis indicated that hardness and fracturability of the extrudates with or without pulp did not show a significant difference. DPPH (2, 2‐diphenyl‐1‐picrylhydrazyl) radical scavenging activity test indicated that antioxidant activity of tomato pulp added extrudates decreased from 16.71 ± 0.42 to 12.84 ± 0.36 μmol Trolox equivalent/g dry weight after extrusion. Total phenol content decreased from 15.37 ± 0.09 to 7.49 ± 0.11 mg gallic acid equivalent/g dry weight after extrusion process. The results suggest that tomato pulp can successfully be added as a functional ingredient to develop new functional extruded food products.